The Effect of Online Game Violence Exposure on Teenagers’ Aggressive Behaviour - Aurora Simanjuntak; Ramaswati Purnawan; Ade Devia Pradipta (Politeknik Negeri Bali, 2021)
This reseacrh aims to analyze the correlation between the exposures of violent scenes in Grand Theft Auto V towards aggressive behavior in teenagers, by posing a central question: how does violence scenes in this game relate to aggressive behavior in teenagers? By using associative quantitative research methods, this research is done through literature study and collecting data in the form of questionnaires. A total of 150 participants who aged 17 to 19 years old and have played Grand Theft Auto V agreed to participate as a respondent. Based on the research, the media exposure dimensions that have been formulated are Frequency, Duration, and Intensity. Aggressive behavior as a form of a teenager’s response to violent scenes has four dimensions: physical aggression, verbal aggression, anger, and hostility. The results of this research indicate that there is a correlation between the exposure Grand Theft Auto V violent scenes towards aggresive behavior in teenagers, with a correlation value of 0.386 which is classified as low. Through this, it can be interpreted that exposure towards Grand Theft Auto V violent scenes contributed 38.6% to aggressive behavior in teenagers.